(3cJGH PgGH GdUhGH aj ESJcJGH Cgd GdcJGHs - (3Ydj Hf GdbWHjf GdTQjajf YHO GdbGOQ GdcjdGfjs ((3Ydi Hf GdHhGH s)
(3ChdgG (B:s
(3hHYO aEf GdHGYK Ydi eGPcQJ hGdMGed Ydi eG hVYJ Cfi QCjJ GdfUGQi hGdjghO ef Cgd GdPeI bO JecfhG ai GdHdGO hCcKQhG ajgG GdaSGO hJcHQhG Ydi GdeSdejf s
(3BNQgG (B:s
(3bGd QShd Gddg Udi Gddg Ydjg hSde (B( (3GdYGajI Ydi YTQI ChLg NeSI ai GdOfjG hNeSI ai GdGNQI aCeG GdJi ai GdOfjG GdYde hGdYHGOI hGdQRb ef GdMdGd hGdUHQ Ydi GdTOI hGdTcQ Ydi GdfYeI hCeG GdJi ai GdGNQI aEfg jCJjg edc GdehJ HdWa hQMeI hjQjMI ai bHQg hds
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG RNGQa s
Keywords: (3GdJhMjO hGdedd hGdfMds